Jondor shevasidagi bazi qarindosh-urug‘chilikka oid so‘zlar - Boltayeva Mahfuza Shukrulla qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this information, the dialectal words related to kinship and kinship used by residents of Jondor district are classified. Each of them is discussed separately, and information about their use and function is given. The influence of the Persian-Tajik language is more noticeable in the following dialectal words related to kinship.